Analisis Implementasi Prinsip Syariah pada Latansa Homestay Kalipuro Kabupaten Banyuwangi berdasarkan Fatwa Dsn-MUI - Ika Maulidina Winedar; Mahmudah Mahmudah; Lutfi Rahmatullah (Rechtenstudent, 2022)
The basis for sharia tourist destination regulations is regulated in the DSN MUI Fatwa No: 108/DSN-MUI/X/2016 concerning guidelines for organizing tourism based on sharia principles. The concept of sharia tourism is the process of incorporating sharia values into the prospects of tourism activities. Sharia tourism must review the basic values of Muslims in its services starting from restaurants, lodging, to tourism activities that refer to sharia where halal and haram are used as the main benchmark. Then how is the implementation of the DSN-MUI fatwa on Latansa Homestay which is the object of study in this study. This type of research is field research using a descriptive qualitative approach. Data collection techniques using observation, semi-structured interviews, and documentaries. Qualitative descriptive analysis of Miles, Huberman and Saldana's interactive model. The results of this study indicate: 1) guests are required to submit ID cards, including for guests who bring partners, must be proven by ID cards with the same address, and for couples who are married in unregistered marriage, they are required to show wedding photos. 2) the food and drinks provided at Latansa Homestay are halal because the place is clean, not unclean, does not contain pork, alcohol, the manager cooks for himself and around the Homestay there are no buying and selling transactions of illegal food and drinks.